Adherence To Covid-19 Preventive Measures Among University Of Ghana Undergraduate Students - Nyamadi, A.A (University Of Ghana, 2022)
ABSTRACT Introduction: The COVID-19 pandemic has caused a lot of morbidity, mortality, and socio-economic losses globally. With no cure in sight, and limited understanding of the vaccines developed against it, adherence to the WHO recommended preventive measures is still necessary to manage the pandemic. Young adults are known to exhibit low adherence toward these measures, although they rapidly spread the disease when infected due to their highly active social networks, and they largely asymptomatic when infected. The paucity of data on adherence behaviour of young Ghanaian adults to the preventive measures warranted this study. Objective: To investigate adherence to COVID-19 preventive measures and associated factors among University of Ghana undergraduate students. Methods: This was a quantitative cross-sectional study involving 303 conveniently sampled on-campus resident undergraduate students of the University of Ghana, using an online self-administered questionnaire. Data was analysed with Stata 16 software. Bivariate analysis using Chi-square/Fisher’s exact tests were performed to test associations between independent variables and adherence to COVID-19 respiratory hygiene, hand hygiene and physical distancing measures. Multiple and Penalized binary logistic regression analysis was done to determine the factors associated with adherence to these measures. A p-value <0.05 was considered significant. Results: 72.9% of students had adequate knowledge of COVID-19 preventive measures, 25.7% had excellent knowledge, and 1.3% had poor knowledge. Respiratory hygiene adherence was the highest (59.1%), followed by physical distancing (21.5%) and hand hygiene (8.9%), while adherence to over 75% of the ten preventive measures assessed was 29%. Positive risk perception (fear of infection) was the only variable significantly associated with hand hygiene adherence; being slightly worried and extremely worried about getting COVID-19 gave 3.8- and 4.4-times odds of adherence to hand hygiene respectively, over never being worried about contracting the disease. (AOR = 2.9, 95% CI = 1.28-11.00, p = 0.016 and AOR = 4.4, 95% CI = 1.44-13.59, p = 0.009 respectively). Conclusion: UG undergraduate students’ adequate knowledge levels of COVID-19 measures did not translate into their adherence behaviour. Authorities can positively influence students’ adherence when they lead by example in adherence, reinforce students’ trust and belief in authorities and science, ensure constant availability of pro-adherent resources, and intensify education on the pandemic.
MPH
Keywords: Covid-19; University Of Ghana; Preventive Measures; Undergraduate Students